THE INFLUENCE OF MENTORS’ GENDER ON THE PSYCHOSOCIAL AND CAREER MENTORING OF WOMEN IN THE SOUTH AFRICAN CONSTRUCTION INDUSTRY - N.R.A. Yokwana; R. Ndihokubwayo; A.O Windapo (Journal of Construction Project Management and Innovation)
This paper examines the influence of gender on the psychosocial and career mentoring of women in the South African construction industry, assessing whether there are statistical significant differences in the mentorship provided, based on gender. A cross-sectional survey approach was adopted in the study; and a purposive sampling method was used to select the female mentees and mentors working in the construction industry. The data collected from this cohort of respondents – who are based in the nine provinces of South Africa – were analysed using descriptive and inferential statistics. The findings suggest that gender plays no role in the successful mentorship of women, as there is no significant difference between the mentorship functions provided by either female or male mentors. Female mentees and mentors were selected independently to participate in the study. However, participants who were in matching mentoring relationships would have brought about improved results. The study provides new knowledge that there is no difference in the mentoring capacity based on gender in the South African construction industry, and that male and female mentors can produce the same level of success.There is no significant difference in the mentoring functions provided by male and female mentors to female mentees. This findings suggest that even though female mentees may be uncomfortable or feel disadvantaged in cross-gender mentorship relationships, these relationships provide the same mentoring benefits to females as those with the same gender. It is, therefore, recommended that female mentees enter crossgender relationships with open minds. The results of this study are limited by the smallness of the sample size. Therefore, further studies would be required to further validate these results. Female mentees and mentors who are in matching mentoring relationships should also be invited to participate in future studies.